COLD WATER IMMERSION AND INFLAMMATORY RESPONSE AFTER RESISTANCE EXERCISES - Missau,Edson (2018)
ABSTRACT Introduction: High-intensity resistance exercises (RE) cause an inflammatory response that reduces functionality. Objective: To evaluate the effects of Cold Water Immersion (CWI) on leukocytosis, oxidative stress parameters, inflammatory markers and delayed onset muscle soreness (DOMS) resulting from a RE session in untrained volunteers. Methods: Thirteen volunteers (aged 26 ± 5 years) who do not engage in RE were randomized and underwent Control RE and RE with CWI sessions. Exercise sessions (leg extension machine, squats and leg presses) consisted of four sets of 10 maximum repetitions (one-week interval between the assessment and the sessions). CWI consisted of immersion in water (15°C) to the umbilicus for 10 minutes immediately after the exercise session. Complete blood count, CRP, creatine kinase (CK) and lipoperoxidation (LPO) were assessed previously (baseline) and immediately, 30 minutes and 2 hours after RE. DOMS was assessed 24 hours after the sessions. Results: RE induced progressive leukocytosis (P<0.001). CRP was elevated 2 hours after exercise (P=0.008) only in the Control RE session. CK increased 30 minutes and 2 hours after exercise (P<0.001) in the Control session, whereas in the CWI session the increase was observed after 2 hours (P<0.001). LPO increased only in the Control session after 2 hours (P=0.025). CWI reduced DOMS by 57% (P<0.001). Conclusion: CWI slows the inflammatory response and reduces DOMS in untrained individuals undergoing RE. Level of Evidence I; Randomized Clinical Trial.